2018
DOI: 10.1377/hlthaff.2017.1658
|View full text |Cite
|
Sign up to set email alerts
|

Electronic Health Records Associated With Lower Hospital Mortality After Systems Have Time To Mature

Abstract: Evidence linking electronic health record (EHR) adoption to better care is mixed. More nuanced measures of adoption, particularly those that capture the common incremental approach of adding functions over time in US hospitals, could help elucidate the relationship between adoption and outcomes. We used data for the period 2008-13 to assess the relationship between EHR adoption and thirty-day mortality rates. We found that baseline adoption was associated with a 0.11-percentage-point higher rate per function. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
51
0
2

Year Published

2018
2018
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 67 publications
(53 citation statements)
references
References 25 publications
0
51
0
2
Order By: Relevance
“…The more experience that clinicians have with EHR systems may be associated with more favorable observations of their effectiveness, 13,16 as well as better patient outcomes. 47 Few rural hospitals were included in our sample which limits conclusions that can be made about EHR use in those hospitals. Recent research suggests a widening divide in adoption of comprehensive EHRs between urban and rural hospitals.…”
Section: Limitationsmentioning
confidence: 99%
“…The more experience that clinicians have with EHR systems may be associated with more favorable observations of their effectiveness, 13,16 as well as better patient outcomes. 47 Few rural hospitals were included in our sample which limits conclusions that can be made about EHR use in those hospitals. Recent research suggests a widening divide in adoption of comprehensive EHRs between urban and rural hospitals.…”
Section: Limitationsmentioning
confidence: 99%
“…Over time, implementation of health IT may lead to benefits for patients as demonstrated by the study by Lin et al 4 , which shows positive outcomes (e.g. hospital mortality) associated with health IT after sufficient time and effort has been spent on implementation, maintenance, and improvement of the system.…”
Section: Introductionmentioning
confidence: 99%
“…CPOE systems are embedded within complex sociotechnical environments that require intentional quality improvement efforts to manifest a reduction in adverse drug events and an improvement in patient safety 8. Similarly, recent work has shown that EHR adoption has a positive effect on patient mortality, but only after a period of acclimation and system maturation 12. Other studies have found that CPOE system may actually contribute to medical errors 13…”
Section: Introductionmentioning
confidence: 99%